Aplikasi Pendekatan Hermeneutika Al-Qur’an Nasr Hamid Abu Zayd terhadap QS. Al-Nisa’ (4): 3 dan Al-Nahl (16): 3-4 - Wely Dozan; Qohar Al Basir (REVELATIA: Jurnal Ilmu Al-Qur'`an dan Tafsir, 2020)
Nasr Hamid Abu Zayd is a Muslim intellectual whose ideas on the Qur’an was contradicting many Egyptian Muslims. He mentioned the Qur'an as a cultural product in the development of Arabic culture because it was revealed gradually according to the situation at that time. Through five contexts, he offered interpretation of the Qur’an that does not distort the text and are based on socio-cultural (hermeneutic). This paper focuses on studying the hermeneutic approach of Abu Zayd and its implications on the interpretation of QS. 4: 3 and 40: 57. The research method is library research by browsing data from books, books, journals and other kinds of literature related to the problem. The results of the study show that hermeneutics can be an alternative methodology for bridging dialogue between text and reality in producing contextual understanding without leaving the Qur’anic chronology and history while obtaining critical understanding. Instead of permitting polygamy, QS. 4: 3, according to him, actually accentuates the context of monogamy. This is in accordance with the context to protect society. Meanwhile, the interpretation QS. 40: 57 that the creation of heavens and earth through al-haq indicates the meaning (materials of creation) instead of creation activity (process).